Numerical Simulation of Multiphase Flow in Steel Continuous Casting Mold Using a Novel Euler–Euler–Lagrange Method. Issue 9 (11th June 2022) - Lai, Qingrui; Luo, Zhiguo; Zhang, Yongjie; You, Yang; Zou, Zongshu
Abstract : Herein, a new Euler–Euler–Lagrange hybrid method is used to simulate the liquid–solid–gas three‐phase flow in a continuous casting mold. In the used method, bubble coalescence and breakup, inclusion aggregation, bubble–inclusion interaction, and complex force balance of bubbles near the solidification front are simultaneously considered. The predicted inclusion size distribution is in good agreement with previous industrial test results. With the application of this method, inclusions can be tracked even if they are collected by bubbles. This characteristic is useful in the study of harmful phenomena in that bubbles are captured by the solidification front after collecting numerous inclusions. Herein, the effects of various simulation factors on results are studied. The descending order of importance of the simulation factors is as follows: bubble–inclusion interaction, bubble coalescence and breakup, and inclusion aggregation. Ignoring any of these factors underestimates the inclusion removal rate and increases the prediction deviation of the inclusion size distribution. Although inclusion aggregation has little effect on the overall removal fraction, it is the most important way to remove small inclusions with a maximum size of 14.14 μm under the conditions of this research. Abstract : In the present study, a new Euler–Euler–Lagrange hybrid method is applied to simulate the liquid–solid–gas (molten steel–solid inclusion–argon bubble) three‐phase flow in the steel continuous casting mold, which considers bubble coalescence and breakup, inclusion aggregation, bubble–inclusion interaction, and complex force balance of bubbles near solidification front at the same time.